AN EXPERIMENTAL STUDY ON FISCHER-TROPSCH CATALYSIS: IMPLICATIONS FOR IMPACT PHENOMENA AND NEBULAR CHEMISTRY - Sekine Y.; Sugita S.; Matsui T.; Shido T.; Yamamoto T.; Iwasawa Y.; Kadono T. (My University, 2006)
Fischer-Tropsch catalysis, by which CO and H2 are converted to CH4 on the surface of transition metals, has been considered to be one of the most important chemical reactions in many planetary processes, such as the formation of the solar and circumplanetary nebulae, the expansion of vapor clouds induced by cometary impacts, and the atmospheric re-entry of vapor condensate due to asteroidal impacts. However, few quantitative experimental studies have been conducted for the catalytic reaction under conditions relevant to these planetary processes. In this study, we conduct Fischer-Tropsch catalytic experiments at low pressures (1.3 × 10-4 bar ≤ P ≤ 5.3 × 10-1 bar) over a wide range of H2/CO ratios (0.25-1000) using pure iron, pure nickel, and iron-nickel alloys. We analyze what gas species are produced and measure the CH4 formation rate. Our results indicate that the CH4 formation rate for iron catalysts strongly depends on both pressure and the H2/CO ratio, and that nickel is a more efficient catalyst at lower pressures and lower H2/CO ratios. This difference in catalytic properties between iron and nickel may come from the reaction steps concerning disproportionation of CO, hydrogenation of surface carbon, and the poisoning of the catalyst. These results suggest that nickel is important in the atmospheric re-entry of impact condensate, while iron is efficient in circumplanetary subnebulae. Our results also indicate that previous numerical models of iron catalysis based on experimental data at 1 bar considerably overestimate CH4 formation efficiency at lower pressures, such as the solar nebula and the atmospheric re-entry of impact condensate. © The Meteoritical Society, 2006.